Empress Maria Theresa and the politics of Habsburg imperial art - Yonan, Michael Elia 1970- (Pennsylvania State Univ. Press, 2011)
"Explores the intersections between monarchy, gender, and art through an investigation of the visual and architectural culture of the eighteenth-century Habsburg empress Maria Theresa"--Provided by publisher.
Includes bibliographical references and index
Keywords: Maria Theresa -- Empress of Austria -- 1717-1780 -- Art patronage; Maria Theresia -- Österreich, Erzherzogin -- 1717-1780; Geschichte 1700-1800; Architektur; Geschichte; Kunst; Politik; Sex role -- Political aspects -- Austria -- History -- 18th century; Art -- Political aspects -- Austria -- History -- 18th century; Architecture -- Political aspects -- Austria -- History -- 18th century; Repräsentation; Höfische Kunst; Österreich; Austria -- Kings and rulers -- Art patronage; Schloss Schönbrunn -- Wien